2017
DOI: 10.1186/s13550-017-0342-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of coronary opacification derived from coronary computed tomography angiography to detect ischemia: first validation versus single-photon emission computed tomography

Abstract: BackgroundEstimation of functional relevance of a coronary stenosis by fractional flow reserve (FFR) from coronary computed tomography angiography (CCTA) has recently provided encouraging results. Due to its limited availability, the corrected contrast opacification (CCO) decrease and the transluminal attenuation gradient (TAG) were suggested as less complex alternatives. The aim of the present study was to assess the accuracy of CCO decrease and TAG to predict ischemia as assessed by single-photon emission co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Likewise, Iguchi et al [27] identified lesion length as a valuable predictor of significant coronary stenosis, which was confirmed in our study (lesion length: OR 1.15, p = 0.037). Furthermore, recent studies by Dey et al [28] and Benz et al [29] identified contrast density difference as the strongest marker for the prediction of lesionspecific ischemia. However, in the present study, contrast density was not evaluated, which might explain the difference in AUCs between the combination of plaque markers (AUC 0.83) and deep machine learning-based CT-FFR (AUC 0.93).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Iguchi et al [27] identified lesion length as a valuable predictor of significant coronary stenosis, which was confirmed in our study (lesion length: OR 1.15, p = 0.037). Furthermore, recent studies by Dey et al [28] and Benz et al [29] identified contrast density difference as the strongest marker for the prediction of lesionspecific ischemia. However, in the present study, contrast density was not evaluated, which might explain the difference in AUCs between the combination of plaque markers (AUC 0.83) and deep machine learning-based CT-FFR (AUC 0.93).…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, CCTA was performed at rest and revealed that the flow at rest might indicate the hemodynamic relevance of coronary lesions, which was consistent with the findings of other scholars. [ 26 , 27 ] These views suggest that measurement of the flow at rest may indicate possible pathological changes following inadequate adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…16 Thanks to significant reduction in radiation exposure from coronary CT angiography, [25][26][27] coronary lesions of younger and healthier patients are now being tested by CT-FFR or other CT-derived measurements. [28][29][30] As a consequence, the interaction between lesion-specific ischemia and myocardial blood flow warrants further investigation to prevent overestimation of coronary lesions.…”
mentioning
confidence: 99%